Evaluation of comparative efficacy of Umeclidinium/Vilanterol versus other bronchodilators in the management of chronic obstructive pulmonary disease: a systematic review and meta-analysis of RCTs - He Zhu; Jiahui Lei; Fan Gao; Yingjie Guo; Limin Zhao (BMC Pulmonary Medicine)
Abstract Background UMEC/VI administered via a combination inhaler is associated with a clinically significant improvement in lung function and health-related quality of life in patients with mild-to-moderate COPD. However, their efficacy compared to other bronchodilator mono or dual therapies still remains unclear. Objective The objective of this research was to evaluate the therapeutic efficacy of UMEC/VI dual and UMEC/VI/FF triple therapies versus alternative bronchodilator regimens in COPD patients. Methods A systematic search was conducted using four electronic databases (PubMed, EMBASE, Scopus, and Cochrane Library) to select publications published in peer-reviewed journals written in English. The odds ratio (OR) and risk ratio (RR) was calculated, along with their 95% confidence intervals. We assessed heterogeneity using Cochrane Q and I [2] statistics and the appropriate p-value. The analysis used RevMan 5.4. Results The current meta-analysis includes 31,814 COPD patients from 17 RCTs. The meta-analysis results demonstrate that the combination of LABA and LAMA provides additive bronchodilation and improved lung function in COPD patients. We found that UMEC/VI dual therapy significantly improved FEV1 (OR 1.98 [95% CI 1.70–2.30]), TDI values (OR 1.97 [95% CI 1.72–2.26]), and reduced SGRQ total scores (OR 1.99 [95% CI 1.71–2.32]), with fewer drug-related adverse events (RR 0.58 [95% CI 0.53–0.64]). Similarly, UMEC/VI/FF triple therapy also showed similar benefits, with significant improvements in FEV1 (OR 1.93 [95% CI 1.73–2.15]), TDI values (OR 2.37 [95% CI 2.15–2.61]), and reduced SGRQ total scores (OR 1.83 [95% CI 1.63–2.05]), and fewer drug-related adverse events (RR 0.53 [95% CI 0.49–0.58]). Conclusion This systematic review and meta-analysis concludes that UMEC and VI combinations are an efficacious treatment option for symptomatic COPD patients.